Acoustic trapping with 3-D manipulation. (1st December 2019) - Liu, Pengfei; Ming, Dong; Tan, Cherie S.; Lin, Bin
Abstract: Non-contact acoustic trapping has evolved to devoid of any mechanical obstacles and shown promising results in many fields such as bio imaging lately. However, in an acoustic field, the movement of the target object is not precisely controlled, which prevents the applications of the acoustic trapping in some fields. Herein, we demonstrate a numerical model for a moving object to specific position in the acoustics, which is coupled by a coded resonant devices array. A double hemispheric arrangement for the devices array can make the focal point stable enough to trapping the object. The modulated wave-front made from the coded resonant devices array generates the shifting in 3-D space. Meanwhile, an acoustic vortex (AV) spanner was used to spin the object simultaneously. When an axisymmetric located at the center of the AV spanner, the rotation is mainly driven by the acoustic radiation force. The radiation torque exerted on a small-radius object is inversely associated with the topological charge in the center acoustic vortex, thereby the radiation torque is enhanced significantly under a larger acoustic vortex and a higher topological charge.